ANTISIPASI DAN MEKANISME PENGAMBILAN KEPUTUSAN PETANI DALAM PENGENDALIAN DAMPAK ANOMALI IKLIM(FARMERS’ ANTICIPATION AND DECISION MAKING MECHANISM IN MANAGING IMPACT OF CLIMATE ANOMALY) - S. Sarjana; M.N. Setiapermas; S. Basuki (PERHIMPI (Indonesian Association of Agricultural Meteorology), 2007)
Farmer’s collective participation in climate anomaly anticipating and managing its impacts are more significant. The study purposed to identify the climate anomaly impact and its anticipation in farmer’s level. The study is conducted in eight districts, i.e., Temanggung, Magelang, Kebumen, Brebes, Kendal, Grobogan, Pati, and Sragen, on July – October 2005. The analysis based on interview of 84 respondents that consist of farmers and officers of local agricultural services. According to the farmers, El Nino affected their farming activities like longer dry season, decreased yield, delay of onset planting season, increased costs for irrigation, seed, pesticides, and cost of land preparation. In farmers’ level, climate anomaly impacts was managed by planting schedules improvement, changing varieties or commodities, and looking for alternative sources of waters. Farmers determine the actions by considering collective decision and the guidance of agriculture extension workers. Time tolerance of farmers tin tailoring climate anomaly is about a month. However, most of farmers manage the farming system based on normal condition. As the climate anomaly is an external factor that affect farming system, local authority should support the farmer’s collective actions through dissemination of anticipation strategies in managing the impacts climate anomaly, and support facilities to implement the strategies.